A benzoxazole compound as a novel MEK inhibitor for the treatment of RAS/RAF mutant cancer. Issue 2 (28th January 2019) - Cheng, Ying; Wang, Xingkai; Xia, Xiangying; Zhang, Wei; Tian, Hongqi
Abstract : Mutations in RAS/RAF occur in large portion of malignancies and are associated with aggressive clinical behaviors and poor prognosis. Therefore, we developed a novel benzoxazole compound (KZ‐001) as a highly potent and selective MEK 1/2 inhibitor. Our efforts were focused on enhancing the activity of the known MEK inhibitor AZD6244 and overcoming the shortcomings existing in current MEK inhibitors. Here we show that compound KZ‐001 exhibits approximately 30‐fold greater inhibition against BRAF‐ and KRAS‐mutant tumor cells than that of AZD6244. These results were also demonstrated using in vivo xenograft models. Furthermore, pharmacokinetics (PK) analysis was performed for KZ‐001, and this compound showed good orally bioavailability (28%) and exposure (AUC0–∞ = 337 ± 169 ng h/mL). To determine its potential clinical application, the synergistic effect of KZ‐001 with other agents was investigated both in vitro and in vivo (xenograft models). KZ‐001 exhibited synergistic anti‐cancer effect in combination with BRAF inhibitor vemurafenib and a microtubule‐stabilizing chemotherapeutic agent docetaxel. In addition, KZ‐001 inhibited the MAPK pathway like known MEK inhibitors. In summary, KZ‐001, a structurally novel benzoxazole compound, was developed as a MEK inhibitor that has potential for cancer treatment. Abstract : What's new? Deregulation of RAS/RAF signaling occurs in a significant proportion of malignancies and is associated with aggressive tumor behavior and poor prognosis, despite the availability of MEK inhibitors targeting the RAS/RAF/MEK/ERK pathway. Here, to overcome limitations in existing MEK inhibitors, the authors synthesized a novel benzoxazole compound, KZ‐001, to selectively inhibit MEK 1/2. In BRAF‐ and KRAS‐mutant tumor cell lines, KZ‐001 inhibited MEK1/2 kinase activity, cellular ERK phosphorylation, and cell proliferation. In vivo, KZ‐001 showed greater antitumor activity than other MEK inhibitors. KZ‐001 further exhibited synergistic anticancer activity when combined with the BRAF inhibitor vemurafenib or the chemotherapeutic agent docetaxel.